Effectiveness of Routine to Research (R2R) in Competency Development among Officials of Health Promotion Operational Support in the Department of Health - Sarawasee, Rakkhwan; Kanyamasa, Songkran (Journal of Health Science of Thailand, 2019)
The Bureau of Health Promotion, Department of Health, had encountered problems in performing support for health promotion operation which included inefficiency, customer dissatisfaction and a lack of cost-saving and time consuming. The underlying cause was identified to be lack of competencies and skills among operating staff. Therefore, in order to solve the problems, there was a need for human resource development with the Bureau; and the Routine to Research (R2R) approach was used as a tool in the process. The objectives of this study were to assess the effectiveness of the R2R in the competency development among officials of the health promotion operation support; to analyze the problems associated with competency development in the year 2015; and to develop, test and evaluate a competency development model that incoporated R2R approach. It was conducted as an action research through classroom activities using the PAOR process which included (1) planning (Plan), (2) action (Act), (3) observation (Observe) and (4) reflection (Reflect). The samples were 30 participants responsible for health operation support in the Bureau of Health Promotion, Department of Health. The study process and data collection tools were R2R learning workshops, self-assessment, after action review (AAR) and data record forms. The data were analyzed by using pair t test. It was found that, after the process, participants had significantly improved R2R knowledge (p<0.05); had significantly more skills to develop R2R research (p<0.05), and had good attitude towards R2R which was utilized in various issues. Using R2R, the health promotion operation support mission was found to be more efficient, less complicated, less cost, and become more satisfaction by the beneficiaries. The participants accepted that the R2R had a positive influence in developing the competencies of the officials and, thus, increased the effectiveness and efficiency of the organization. Therefore, R2R should be routinely promoted. To facilitate the process, officials of the Department of Health should pay attention on keeping and collecting data relating to situation and problems generated from their routine tasks so that the data could be utilized for R2R research work. Such process would help improving staff’s competency and quality of the routine performance which would lead to higher efficiency and innovative outcomes of the Department of Health.